Determination of Environmental Impact and Optimum Thickness of Insulation for Building Walls - Ucar, Aynur; Balo, Figen (Wiley, 2011)
The optimum insulation thickness of the external walls, energy cost savings over a lifetime of 10 yr, and payback periods are calculated for the four different wall types in the city of Elazig., Turkey. The net energy cost savings is calculated by using the P-1-P-2 method. According to the results, the optimum insulation thickness has been obtained by using coal as the energy source and stropor as the insulating material. The results show that the optimum insulation thicknesses vary between 4.5 and 16.5 cm, energy cost savings vary between 14 and 22 $/m(2), and payback periods vary between 1.5 and 2 yr depending on the wall type. The highest value of energy cost savings is reached for the Wall III, which has a composite structure called a sandwich wall. The emissions of CO2, SO2, CO, and NOx from the combustion of coal are calculated for the four different wall types. It has been determined that when the optimum insulation thickness is used for coal as an energy source in Elazig., the CO2 emission rates of fuel vary between 8.3 and 9.3 kg/m(2) yr and the SO2 emission rates of fuel vary between 0.017 and 0.019 kg/m(2) yr depending on the wall type. The emissions of CO and NOx are reduced by 82% by applying this optimum insulation thickness. (C) 2010 American Institute of Chemical Engineers Environ Prog, 30: 113-122, 2011
Keywords: optimum insulation thickness; energy cost savings; life cycle cost; environment